ANALISIS KEMAMPUAN MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR DALAM MENGERJAKAN SOAL – SOAL FINANCIAL NUMERACY - Fatmawilda, Fatmawilda; Putra, Zetra Hainul; Witri, Gustimal; Hidayah, Hikmah (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2024)
This research aims to measure the ability of elementary school teacher education students in working on financial numeracy questions. The research method used was a quantitative survey research method with data collection using a 20-question financial numeracy test method which was distributed to 37 respondents. The questions answered correctly by all respondents were questions number 1, 13, 14 and 15 with the indicator aspect of consumption. This is because financial numeracy questions with consumption indicators are relatively easy to do because they relate to everyday life. Meanwhile, questions 2, 3 and 16 have the highest level of difficulty. This can be seen from the number of respondents who could only answer the questions correctly as 10 people because the questions given required strong concentration and understanding in order to solve the questions well, therefore the right strategy was needed to understand the theory first. Overall, all respondents responded well to the financial numeracy questions to support the learning process, so it can be concluded that prospective elementary school teacher students have a good understanding in writing financial numeracy questions and will later be able to apply this to students as teachers.